2018
DOI: 10.1210/en.2018-00108
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of A-Type K+ Channels by Urotensin-II Induces Sensory Neuronal Hyperexcitability Through the PKCα-ERK Pathway

Abstract: Previous studies have implicated urotensin-II in the nociception of sensory neurons. However, to date the relevant mechanisms remain unknown. In the current study we determined the role of urotensin-II in the regulation of transient outward A-type potassium currents (IA) and neuronal excitability in trigeminal ganglion (TG) neurons. We found that application of urotensin-II to small-diameter TG neurons decreased IA in a dose-dependent manner, whereas the delayed rectifier potassium current was unaffected. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…4f and g). The I A in sensory neurons is thought to be mediated by Kv1.4, Kv3.4, Kv4.1, Kv4.2, and Kv4.3 channels, among which the Kv4.2 subunit is negligibly expressed [25, 4143]. In this study, we examined the expression of Kv4 subunits (Kv4.1, Kv4.2, and Kv4.3) as well as that of Kv1.4 and Kv3.4 in rat TG tissues by RT-PCR analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4f and g). The I A in sensory neurons is thought to be mediated by Kv1.4, Kv3.4, Kv4.1, Kv4.2, and Kv4.3 channels, among which the Kv4.2 subunit is negligibly expressed [25, 4143]. In this study, we examined the expression of Kv4 subunits (Kv4.1, Kv4.2, and Kv4.3) as well as that of Kv1.4 and Kv3.4 in rat TG tissues by RT-PCR analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested the differential expression profile of Kv subunits in different classes of sensory neurons. The I A in sensory neurons is thought to be mediated by Kv1.4, Kv3.4, Kv4.1, Kv4.2, and Kv4.3 channels [25, 41, 42]. Interestingly, both strong Kv4.3 immunoreactivity in small-sized TG neurons [42] and a large number Kv1.4-positive neurons in the TGs [56] have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I A encoded by Kv channels plays pivotal roles in modulating membrane excitability in multiple excitable cell types, including TG neurons (15,23). To determine the functional roles of the I A decrease mediated by MC4R activation, we investigated whether ␣-MSH application might affect the neuronal excitability.…”
Section: ␣-Msh Enhances Tg Neuronal Excitability Through I a Modulationmentioning
confidence: 99%